Transformações de fase termoelásticas em ligas com memória de forma a base de Cu-Al-Ni - Mazzer, Eric Marchezini (2016)
Shape memory alloys (SMA) have some exceptional properties such as the shape memory effect and the superelasticity. Both are associated with a martensitic/austenitic phase transformation. Alloys of the system Cu-Al-Ni, Cu- Zn-Al and NiTi belong to this class of material. The interest in the study of Cubased SMA arises from the fact that they are cheaper than NiTi and might achieve better properties in specific applications. Considering the presented facts, the aim of the thesis is to understand the phase transformation and its features such as the stabilization and hysteresis using thermoelastic thermodynamics and a theory of the compatibility between the austenite and martensite for the system Cu-Al-Ni. This system attracts attention of the scientific community because it is a good candidate in the application of high temperature shape memory alloys (HTSMA), working above 100 oC. Another aim of the thesis is to evaluate the mechanical and functional properties of one alloy processed by spray forming, which was selected based in on the previous study. Important correlations were observed on the thermodynamics and crystallographic compatibility with the phase transformation characteristics of the system Cu-Al-Ni, which also enabled the production of an alloy with good functional properties regarding the shape memory effect.